"Ground‐cherry" appearance of the pulmonary trunk: Incidentally detected sinoatrial nodal branch‐to‐pulmonary trunk fistula. Issue 5 (25th February 2022) - Mukherjee, Aprateem; Pandey, Niraj Nirmal; Kumar, Sanjeev
Abstract: We present a case of a 45‐year‐old man with atypical chest pain who underwent coronary computed tomography angiography which incidentally revealed a conglomerate of nondilated tortuous vessels along the inferior half of the surface of the pulmonary trunk, resulting in a "ground‐cherry" like ridged appearance. Tracing these vessels proximally and distally revealed it to be arising from the sinoatrial nodal branch of the right coronary artery and distally draining into the left anterolateral aspect of the pulmonary trunk.